Tastes of revolution, change and love: codes of consumption in fiction from new China - Henningsen, Lena (Frontiers of literary studies in China, 2014)
This paper analyses Socialist Realist novels from the early years of the People’s Republic of China (PRC), focusing on scenes of food and drink consumption. While these scenes may appear marginal at first glance, the analysis demonstrates how food and its consumption function as codes to normative values. I am therefore proposing a reading of these texts based on the model of intertextuality (Julia Kristeva) and on an anthropological model on (food) consumption (Mary Douglas), advocating that acts of consumption reveal social hierarchies and the position of the individual therein. These fictional scenes of everyday activities construct fictional characters as heroes or villains. Given the normative value of this officially endorsed literature, these scenes at the same time prescribe (and, likewise, proscribe) certain behavior to their readers. On another level, however, these codes also convey information that could not be openly spelled out at the time, as when the sharing of food is the only way in which two fictional characters can express their love. Simple food can thus be the source of entertainment, enjoyment, suspense, and even nostalgia for contemporary readers, which, in turn, may be one of the reasons for the lasting popularity of the codes described and of a number of the texts presented in the analysis.
Gesehen am 21.04.2020